Abundance and Distribution of Sharks in Northeast Florida Waters and Identification of Potential Nursery Habitat. Issue 1 (6th September 2013) - McCallister, Michael; Ford, Ryan; Gelsleichter, James
Abstract: Sharks are considered top predators in many marine ecosystems and can play an important role in structuring community ecology. As a result, it is necessary to understand the factors that influence their abundance and distribution. This is particularly important as fishery managers develop management plans for sharks that identify areas that serve as essential fish habitat, especially nursery habitat. However, our understanding of shark habitat use in northeast Florida waters is limited. The goal of this study was to characterize the abundance and distribution of sharks in northeast Florida estuaries and to examine the effect of abiotic factors on shark habitat use. A bottom longline survey conducted from 2009 to 2011 indicated that 11 shark species use the estuarine waters of northeast Florida during the summer months. Atlantic Sharpnose Sharks Rhizoprionodon terraenovae, Blacktip Sharks Carcharhinus limbatus, and Bonnetheads Sphyrna tiburo were the most abundant species and made up 81.4% of the total catch. Site, month, and bottom water temperature were the most important factors determining the presence and abundance of sharks and suggest both regional and seasonal variations in the use of northeast Florida waters. Depth, salinity, and dissolved oxygen were also important factors. Our data show that these waters serve as a nursery for Atlantic Sharpnose and Blacktip Sharks, with young‐of‐the‐year and juveniles being present in the summer months. Limited tag–return data reveal that juvenile sharks remain in these waters throughout the summer and that some return in subsequent summers. This is the first study to characterize the abundance and distribution of sharks and identify potential nursery areas in northeast Florida estuaries. Received October 10, 2012; accepted March 7, 2013